#### Answer

27

#### Work Step by Step

We are given the expression $8k-3m$. We are also given that $k=3$ and $m=-1$. We can plug in these values to the expression in order to evaluate.
$8(3)-3(-1)=(8\times3)-(3\times-1)=24-(-3)=24+3=27$

Published by
Pearson

ISBN 10:
0134467795

ISBN 13:
978-0-13446-779-5

27

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.